Collaborative governance in prevention of the spread of pulmonary tuberculosis in Serdang Bedagai district in 2024 - Surya, Welong S.; Damanik, Balqis Nurmauli (Science Midwifery, 2024)
Preventing the spread of pulmonary tuberculosis (TB) in Serdang Bedagai Regency in 2024 requires a collaborative governance approach involving various stakeholders. Based on the Global TB Report 2023, Indonesia ranks second in the world in the number of TB cases, with an estimated 1,060,000 new cases and 134,000 deaths per year (Kork et al., 2021). TB prevention efforts must involve the health and non-health sectors simultaneously, with the aim of finding and treating all TB cases until cured. This study uses a qualitative descriptive method with data collection techniques through interviews and literature studies, involving informants from various government agencies and community organizations. The results of the study show that there are three main elements in collaborative governance: principled engagement, shared motivation, and capacity for joint action. Principled engagement includes open and inclusive communication between stakeholders, while shared motivation is characterized by mutual trust and understanding between actors. The capacity for joint action involves procedures, leadership, knowledge, and resources coordinated by the local government. This study emphasizes the importance of cross-sector collaboration to achieve TB elimination in Indonesia by 2030.